2009
DOI: 10.1063/1.3186640
|View full text |Cite
|
Sign up to set email alerts
|

Electro-optical light scattering shutter using electrospun cellulose-based nano- and microfibers

Abstract: Electrospun cellulose-based nano and microfibers and a nematic liquid crystal are used to assemble an electro-optical (EO) light-scattering device that shows enhanced characteristics when compared to similar devices. Based on the controlled scattering of light in the composite system, the device can achieve light transmission coefficients tunable from 1% up to around 89%. Simulation of the EO behavior indicates that the roughness of the polymer-liquid crystal interface is crucial for the optical performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 9 publications
(10 reference statements)
0
22
0
Order By: Relevance
“…However, experiments with pure thermotropic liquid crystals have shown that the orientational anisotropy of nematics alone does not affect the filament stability [4,6,15]. Even a smectic layer structure in the conventional smectic-A (SmA) liquid crystals of rodshaped molecules can only slightly improve the stability of the LC fibers in air [13,14,16,17]. A single liquidcrystalline system forming freely suspended filaments previously reported was a discotic LC stabilized by its 1D columnar order [4,8,15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, experiments with pure thermotropic liquid crystals have shown that the orientational anisotropy of nematics alone does not affect the filament stability [4,6,15]. Even a smectic layer structure in the conventional smectic-A (SmA) liquid crystals of rodshaped molecules can only slightly improve the stability of the LC fibers in air [13,14,16,17]. A single liquidcrystalline system forming freely suspended filaments previously reported was a discotic LC stabilized by its 1D columnar order [4,8,15].…”
mentioning
confidence: 99%
“…For instance, natural silk is initially spun from a lyotropic nematic liquid. Another example of a liquid-crystalline fiber-forming material is cellulose, which can be electrospun from a cholesteric solution [12][13][14]. However, experiments with pure thermotropic liquid crystals have shown that the orientational anisotropy of nematics alone does not affect the filament stability [4,6,15].…”
mentioning
confidence: 99%
“…Considerable kinds of polymer matrixes have been used for PDLC films, such as poly(methyl methacrylate-co-butyl acrylate), poly(methyl methacrylate), NOA65, polyacrylonitrile, and E-51 biphenol-A epoxy resin [4][5][6][7][8][9]. Of all these polymer matrixes, the bisphenol-A epoxy resin with two phenol functional groups, has received attention owing to their excellent chemical and physical properties, such as electric insulation, resistant to corrosion and adhesion to ITO glasses used in the PDLC cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, spun fibers can be almost aligned in one direction on the collector wheel with high-speed rotation [27]. The application to the LC devices, for instance, a CPDLC mode which can apply to as a privacy window by using the cellulose fibers has been proposed [28]. The purposes of this paper are performed to determine the condition of forming the layer consisted of uniaxis PVCi fibers by the ES treatment and the proffer of a novel technique for forming the bistable layer consisted of PVCi fibers by applying the photo-alignment technique.…”
Section: Introductionmentioning
confidence: 99%